Ritual and Trauma in Toni Morrison’s Beloved - Neupane, Khagendra (The Outlook: Journal of English Studies, 2026)
This article interprets ritual as a healing process of trauma in Toni Morrison’s Beloved. It shows how slavery harms African Americans mentally, culturally, and across generations. It focuses on how Morrison employs communal ritual as a way of healing such wounds. The study examines Sethe’s painful memory, Beloved’s haunting presence, and the community’s role in helping the healing process. It uses a qualitative textual approach to analyze storytelling, memory, bodily expression, spiritual gathering, and exorcism as ritual practices through which suppressed pain is recognized and transformed. . The article argues that Morrison presents healing as a shared cultural and spiritual process shaped by African American memory and community support. In this way, Beloved presents ritual as a restorative practice through which trauma is voiced, communal bonds are renewed, and historical memory becomes a source of survival.